Different clinical presentation of intralabyrinthine schwannomas - a systematic review - Elias,Thaís Gomes Abrahão (2019)
Abstract Introduction: Intralabyrinthine schwannoma is a rare, benign tumor that affects the most terminal portions of the vestibular and cochlear nerves. This tumor can be classified into 10 subtypes, according to its inner ear location. Objective: To carry out a comprehensive review of the most frequent auditory manifestations secondary to the intralabyrinthine schwannoma, describing the possible underlying pathophysiological mechanisms. Methods: Systematic review of the literature until October 2017 using the PubMed, Web of Science and Scopus databases. The inclusion criteria were clinical manifestations of the intralabyrinthine schwannoma. Three researchers independently assessed the articles and extracted relevant information. The description of a case of an intravestibular subtype intralabyrinthine schwannoma with multiple forms of clinical presentations was used as an example. Results: Twenty-seven studies met our inclusion criteria. The most common intralabyrinthine schwannoma subtype was the intracochlear, followed by the intravestibular type. All the cases demonstrated hearing loss, usually progressive hearing loss. Conclusion: The diagnosis of intralabyrinthine schwannomas is based on high-resolution magnetic resonance imaging and should be included in the differential diagnosis of patients with vestibulocochlear complaints. Although there are approximately 600 cases in the literature, we still lack a detailed description of the clinical evolution of the patients, correlating it with MRI findings of temporal bones and tumor subtype.